Prerequisites for the legal mechanisms development to combat disinformation in social media in the context of national security: problem statement - A. I. Marushchak (Bulletin of Kharkiv National University of Internal Affairs, 2021)
The article deals with the preconditions for the legal mechanisms development to combat disinformation in social media in the context of national security. The conclusion is formulated on the necessity of the development of such mechanisms on the basis of constitutional freedom of speech principle, with legislative definition of the exclusive possible restriction list in social media for the sake of national security.It is noted that the difference between legal and corporate internal norms of regulation of social media companies directly affects the effectiveness of national interests’ protection both in the United States and Ukraine. Because the non-binding provisions of the First Amendment of the US Constitution for private entities determine the orientation of social media companies to make a profit, although the policy of Facebook and Google adheres to the principles of freedom of speech.In the context of capacity building of the Centre for Countering Disinformation, counteracting disinformation campaigns for national security reasons requires a combination of efforts of the Centre with the national cybersecurity system, and with regulatory bodies of the media, strategic communications units of Ukraine Government in close cooperation with the private sector, primarily social media companies, and civil society.It is concluded that compared to the US government, Ukrainian government has broader constitutional preconditions for the national security interests’ protection, particularly in connection with Russian Federation aggression. It is noted that regulations on combating disinformation in social networks should take into account international human rights requirements, national interests, as well as business processes of social media companies.